理学・作業療法学科の学生に対する効率的人体解剖見学実習 - 木村 智子; 松田 和郎; 相見 良成; 瀧 公介; 本間 智; 宇田川 潤; 工藤 基 (形態・機能, 2012)
At Shiga University of Medical Science, we have recently started practice visits to human dissection classes for co-medical students. As the number of co-medical schools that including an increase in human dissection classes, various problems are therefore expected to occur. We therefore established an educational method to optimize the effectiveness of such classes. For PT / OT students and the attending teachers who participated in dissection classes in 2010, we conducted an investigation regarding the efficacy of our teaching method. According to the survey results, many favorable opinions were obtained about our presentation and seminar methods, in which we showed the learning points in advance of the dissection classes. Such learning was found to not only increase student motivation, but it also enabled students to better understand the cadaver donation system.  These classes are taught to students the importance of maintaining privacy and secrecy at the highest levels. Therefore, it became clear that our teaching methods, for PT / OT students, to be extremely effective. According to this survey, many PT/OT students preferred locomotor system oriented training, and requested an increase in the length of time for such dissection classes. We therefore plan to continually improve on the our program so that PT / OT students may obtain the most benefits from such human dissection classes. 滋賀医科大学では、これまでコ･メディカル学生に対する解剖学教育の一環として、人体解剖見学実習を受け入れてきたが、見学実習を希望するコ･メディカル養成校も増え、人的負担、時間的制約などの問題が生じてきた。そこで、これらの問題を解決すべく、滋賀医科大学では2010年度よりコ･メディカル学生への人体解剖見学実習の提供方法を工夫して実施してきた。今回、我々は2010年度に人体解剖見学実習へ参加したPT･OT学生ならびに引率教員を対象に、実施方法の有効性についてアンケート調査を行った。実習の提供方法に関する結果は、セミナー方式や見学ポイントの提示について多くの肯定的意見が得られ、すべての学生で学習意欲が高まり、献体制度や守秘義務の理解度も非常に高いことが見出された。総じて、PT･OT学生に対してセミナー方式や見学ポイントを提示した上で見学実習の機会を与えることは極めて有効な教育方法であることがアンケート結果から明らかになった。一方、運動器系の内容充実を求める意見や、より多くの見学時間を求める意見もあったことから、我々はPT･OTのニーズに合わせた見学カリキュラムの作成や実施時期・時間などについて改善する必要性があることも明らかになった。